Religion Studies: From University to School - Goldburg, Peta (Journal for the academic study of religion, 2009)
As a religious educator I am passionate about the teaching of religion in the school sector and I see the Study of Religion as a critical component in the education of all students. I believe all schools should teach religion; that all students should be engaged in the critical study of religion; and that we need continually to shape and re-shape the ways in which religion in schools is taught. The paper is in three sections. The first section comments on the teaching of religion in schools and in particular traces the shift in teaching styles from enfaithing (Lovat 2002) approaches to educational approaches. The second section centres on the development of Study of Religion courses in the senior years of secondary schools and the growing popularity of such courses. In the third section, I will offer a critique of current practice in the area of Study of Religion in schools and suggest some ways forward which I believe will strengthen the teaching of Study of Religion.